Perancangan Prototipe Antarmuka Pengguna pada Aplikasi E-Commerce Pertanian Berbasis Mobile - Diaz Agil Prasetyo; Carissa Xyla Oxaveria; Shinta Aulia; Nicko Richardo; Muhammad Reynaldi Dwi Saputra; Rahmi Yulia Ningsih; Chairani Putri Pratiwi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The use of e-commerce applications in the agricultural sector has not been optimized due to farmers' low understanding of technology and a less user-friendly interface design. This research aims to design a prototype mobile-based e-commerce application interface that suits the needs of farmers. The Design Thinking method is used to understand user needs and develop intuitive solutions. The results showed a friendly interface design for farmers with low digital literacy, thus supporting the adoption of e-commerce applications in the agricultural sector. This research contributes to the increased utilization of technology in the distribution of farm produce and helps improve the welfare of farmers.